Kekuatan Jenis Kelamin Terhadap Pola Perilaku Konsumsi Islam Mahasiswa Ekonomi Islam Universitas Negeri Surabaya - Larasati, Ayu; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2020)
This study aims to determine the strength of gender to Islamic consumption behavior of Islamic Economics students, Surabaya State University. Islamic consumption behavior measured by the five basic principles of consumption in Islam. This study uses quantitative descriptive method. The research sample set were 146 students but only 91 students could be further processed. Data source were obtained from questionnaires with guttman scale and analyzed by probit regression using Stata 14. The result showed that woman have a higher probability of behaving in Islamic consumption than man.